1
$\begingroup$

I was solving a problem to discover n and after I transformed the problem it gave me this equation:

\begin{equation*} \left\lfloor{\frac{2}{3}\sqrt{10^{2n}-1}}\right\rfloor = \frac{2}{3}(10^{n}-1) \end{equation*}

So I tried to simplify it by defining: \begin{equation*} k = 10^{n}-1 \end{equation*}

and was left with: \begin{equation*} \left\lfloor{\frac{2}{3}\sqrt{k(k+2)}}\right\rfloor = \frac{2}{3}k \end{equation*}

But I can't get past that. Can anyone help me?

$\endgroup$
2
$\begingroup$

Hint: $10^n-1$ is a multiple of $9$, so $\frac{2}{3}k$ is an integer, then:

$$ \begin{align} \left\lfloor{\frac{2}{3}\sqrt{k(k+2)}}\right\rfloor = \frac{2}{3}k \;\;&\iff\;\; \frac{2}{3}k \le \frac{2}{3}\sqrt{k(k+2)} \lt \frac{2}{3}k \,+\, 1 \;\; \\ &\iff\;\; \frac{4}{9}k^2 \le \frac{4}{9}(k^2+2k) \lt \frac{4}{9}k^2 + \frac{4}{3}k+1 \\ &\iff\;\; 0 \le \frac{8}{9} k \lt \frac{4}{3}k+1 \\ \end{align} $$

$\endgroup$
1
$\begingroup$

Note that $$-8(10^n-1)\ \le\ 0\ <\ 4\cdot10^n+5$$ is true for all $n\in\mathbb Z^+$. In other words $$-8\cdot10^n+4\ \le\ -4\ <\ 4\cdot10^n+1$$ $$\iff\ 4(10^n-1)^2\ \le\ 4(10^{2n}-1)\ <\ (2\cdot10^n+1)^2$$ $$\iff\ 2(10^n-1)\ \le\ 2\sqrt{10^{2n}-1}\ <\ 2\cdot10^n+1$$ $$\iff\ \frac23(10^n-1)\ \le\ \frac23\sqrt{10^{2n}-1}\ <\ \frac{2\cdot10^n+1}3=\frac23(10^n-1)+1$$ $$\iff\ \left\lfloor\frac23\sqrt{10^{2n}-1}\right\rfloor\ =\ \frac23(10^n-1)$$ since $10^n-1$ is a multiple of 9 and so is divisible by 3. Hence your equation is true for all non-negative integers $n$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.